1999
DOI: 10.1007/s005310050244
|View full text |Cite
|
Sign up to set email alerts
|

Tectono-thermal evolution in a region with thin-skinned tectonics: the western nappes in the Cantabrian Zone (Variscan belt of NW Spain)

Abstract: The palaeotemperature distribution in the transition from diagenesis to metamorphism in the western nappes of the Cantabrian Zone (Somiedo, La Sobia and Aramo Units) are analysed by conodont colour alteration index (CAI) and illite crystallinity (IC). Structural and stratigraphic control in distribution of CAI and IC values is observed. Both CAI and IC value distributions show that anchizonal conditions are reached in the lower part of the Somiedo Unit. A disruption of the thermal trend by basal thrusts is evi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 21 publications
1
33
0
Order By: Relevance
“…3) clearly indicated that the assumption about the latest Carboniferous-Permian heating allowed the best-fit calibration in all modelled samples (P37, P60, and P89). Previous studies applying different methods (clay minerals, fluid inclusions, vitrinite reflectance) in SCZ and the Sabero Coalfield have also led to similar conclusions (Bastida et al 1999;Ayllon et al 2003;Ayllon 2003;Frings et al 2004;Aller et al 2005;Colmenero et al 2008;Botor et al 2009;Botor 2012). Heating to temperatures of at least 110 °C caused the complete resetting of AFT ages.…”
Section: Discussionmentioning
confidence: 55%
See 4 more Smart Citations
“…3) clearly indicated that the assumption about the latest Carboniferous-Permian heating allowed the best-fit calibration in all modelled samples (P37, P60, and P89). Previous studies applying different methods (clay minerals, fluid inclusions, vitrinite reflectance) in SCZ and the Sabero Coalfield have also led to similar conclusions (Bastida et al 1999;Ayllon et al 2003;Ayllon 2003;Frings et al 2004;Aller et al 2005;Colmenero et al 2008;Botor et al 2009;Botor 2012). Heating to temperatures of at least 110 °C caused the complete resetting of AFT ages.…”
Section: Discussionmentioning
confidence: 55%
“…The syn-orogenic Carboniferous pile has been interpreted as a foreland basin sequence (Julivert 1971;Marcos and Pulgar 1982). Both successions were folded and thrust between Westphalian B and Stephanian times (Julivert 1971;Pérez-Estaún et al 1988;Bastida et al 1999). The main period of the Variscan deformation ended around 300 Ma, based on recent palaeomagnetic data that record the oroclinal bending of the Variscan Ibero-Armorican Arc ( Van der Voo et al 1997;Weil et al 2001Weil et al , 2010.…”
Section: Geological Settingmentioning
confidence: 99%
See 3 more Smart Citations